2016
DOI: 10.4149/bll_2016_030
|View full text |Cite
|
Sign up to set email alerts
|

What is the neutrophil/lymphocyte ratio in sarcoidosis?

Abstract: AIM: Information regarding the Neutrophil/Lymphocyte ratio (NLR) in sarcoidosis and the data from studies recommending its use as an indicator of infl ammation and in the differential diagnosis and prognosis, are limited. With this study, it was aimed to obtain data regarding the NLR level in the patients at the time of presentation to the hospital and to determine the characteristics of patients in whom the NLR value was > 2. RESULTS: During the study period, of the 3434 patients with the sub-diagnosis of D86… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 14 publications
(22 reference statements)
0
9
0
Order By: Relevance
“…The NLR is novel prognostic, diagnostic marker for inflammatory diseases 11,13,14,23 . In the study by İliaz et al, the NLR was found to be supportive in differentiation between tuberculosis and sarcoidosis with the cutoff value of 2.55 13 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The NLR is novel prognostic, diagnostic marker for inflammatory diseases 11,13,14,23 . In the study by İliaz et al, the NLR was found to be supportive in differentiation between tuberculosis and sarcoidosis with the cutoff value of 2.55 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophil to lymphocyte ratio (NLR) has been recently emerged as a cost-effective, potential inflammatory marker and found to be associated with the severity and prognosis of systemic inflammatory diseases, cancer, and respiratory and cardiac diseases. Although there are a limited number of studies, NLR was shown to be increased in patients with sarcoidosis as compared with the control group 4,5,13,14 .…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…The neutrophil/lymphocyte ratio (NLR), platelet count/mean platelet volume (PLT/MPV) ratio, and the platelet count/ lymphocyte ratio (PLR), which may be estimated from hemogram results, have been examined for their role in the diagnosis, treatment response, and severity of respiratory system diseases. NLR, PLR, and PLT/MPV values have been examined in chronic obstructive pulmonary disease (COPD) by investigators at this center, [11][12][13][14] as well as in sarcoidosis [15,16] and interstitial lung diseases. [17] Chronic inflammatory diseases with respiratory system involvement, such as RA and other CVD, are known to have similar symptoms and signs.…”
Section: Introductionmentioning
confidence: 99%